البطاقات الالكترونية ودورها في تحسين الخدمة المالية - التجاني, حنان (University of eloued جامعة الوادي, 2019)
يعد تحديث نظام الدفع أولوية هامة لجميع الاقتصاديات ما دام أن وسائل الدفع التقليدية أصبحت أقل فاعلية في معالجة المعاملات لاسيما بظهور المصارف الإلكترونية، فالتطور التكنولوجي ساعد كثيرا في إنشاء وسائل دفع جديدة كبطاقات الائتمان، الشيكات الإلكترونية والنقود الإلكترونية ( محفظة النقد الإلكتروني) والتي من شأنها تسهيل مهمة تسوية المعاملات المالية. الجزائر لم تشذ عن هذه القاعدة، فقد شهد بريد الجزائر تطورات تتماشى وهذه التكنولوجيا الحديثة فكان لابد لها من الإرتقاء بنظامها الى مستوى تلك التطورات وبالتالي تحديث نظام الدفع وذلك لتحسين الخدمات المالية التي يقدمها بريد الجزائر عن طريق إصدار وسائل دفع حديثة تمثلت بداية في البطاقة المغناطسية (الكلاسيكية) التي لم تلقى إقبالا كبيرا عليها من طرف الزبائن ومن أجل تقديم خدمات تلبي رغبات العملاء قام بريد الجزائر بإصدار البطاقة الذهبية والتي تقدم خدمات جديدة لم تكن متوفرة في البطاقة القديمة ( التحويل من حساب لآخر، تسديد الفواتير ...) فقدساهمت هاته البطاقة بصفة كبيرة في تحسين الخدمات المالية التي يقدمها بريد الجزائر. The modernization of the paement system is an important priority for all economies as long as the traditional means of payment are less effective in dealing with transactions, especially with the advent of electronic banks, technological development has greatly helped to create new payementmethods such as credit cards, electronic cheques and cash electronic (e-cash wallet) that facilitates the task of settling financial transactions. Algeria did not deviate from this rule, Algeria's poste witnessed development in line with this modern technology, and it had to upgrade its system to the level of those developments and thus modernize the payment system to improve the financial services provided by the poste of Algeria through the issuance of modern means of payment, which was the beginning in the magnetic card (classical),which has not received a great turnout by the customers and in order to provide services to meet the wishes of the customers, the posteof the gold card, which offers new service that were not available on the old card (transfer from one account to another, payment of invoices…), lost this card contributed significantly Algeria.to the improvement of the financial services provided by the post of
مذكرة ماستر تخصص اقتصاد نقدي وبنكي
Keywords: البطاقة الالكترونية، الدفع الالكتروني، خدمات مالية، الصراف الآلي، البطاقة الذهبية، بريد الجزائر (وكالة الوادي); E-card, electronic payement, financial services, ATM, gold card, Algeria post (eloued Agency).